Early Metrics of Return on Investment of North American Skull Base Society Research Grant Funding, 2018–2024 - Hsiao, Zoe; Tsang, Cynthia; Renteria, Alondra; Richardson, Angela M.; Zwagerman, Nathan T.; London, Nyall R., Jr.; Bi, Wenya Linda; Kuan, Edward C. (Journal of Neurological Surgery Part B: Skull Base, 2025)
This study aimed to understand the impact of the North American Skull Base Society (NASBS) Research Grant on recipients' research productivity.A survey was sent to NASBS Research Grant recipients, and recipients' curriculum vitae (CV) were collected. The main outcome measures of this study are the amount and types of funding received after the NASBS project completion.From 2018 to 2024, 28 first-time recipients of the NASBS Research Grant received a total of $399,083 in funding. Of the 28 recipients, 20 responded to the survey, and 16 submitted CV data. Among the CV data, there were 12 grants awarded following NASBS project completion, which amounted to a ratio of $1 of NASBS funding to $35.22 of subsequent funding in the program's initial 7 years. The adjusted ratio excluding outliers was $1 to $4.01. Most of the subsequent funding was from industry grants, which accounted for 79.2% of total dollars, and National Institutes of Health (NIH) grants, which accounted for 15.0% of total dollars. NASBS grants have funded projects that led to 19 original research articles among the 28 first-time recipients. Subjectively, recipients had a positive perspective of the grant, and on a five-point Likert scale, the majority strongly agreed that they would encourage other NASBS members to apply for the grant (mean ± standard deviation = 4.79 ± 0.71).The NASBS Research Grant has been a positive opportunity for its recipients as reflected in subsequent success in obtaining research funding, as well as in the perspective recipients had towards the award.
Keywords: North American Skull Base Society; skull base; research funding; career development; National Institutes of Health funding